(untitled) (Sociologisk Forskning, 2023)
The aim of the present article has been to explore how the public is encouraged to engage emotionally in criminal policy matters. By comparing how two of the largest political parties in Sweden – the Moderate Party and the Social Democratic Party – express emotions during the 2018 election campaigns, the article has illustrated an emotional political struggle over voters. Even though worry and (dis)trust are prominently articulated emotions by both political parties, they address these emotions in different ways and the parties also differ regarding which emotions they encourage in the public. The Moderate Party describes worry and distrust as a result of a correct evaluation of society’s state, the constituted solution being to change social conditions through an advancement of state control. Instead, The Social Democratic Party portrays worry as a result of the uncertainty of the future, and the party encourage the public to invest in trust in others to overcome this worry.